História, memória e patrimônio cultural: fundamentos e sensibilizações da comunidade de Nova Palma (CPG e Museu Histórico). - Stefanello, Liriana Zanon (2010)
Along of times and of history, we observated the transformation of several conceptions and proper society. This is perceived, for example, in comprehensions of cultural patrimony, of history and of museum. In this sense, this study presents the importancy of historical basis to museum institution. While memory referency, of history and thus of community identity. Community identified in this study, as The Fourth Imperial Colony of Italian Immigration in the State of Rio Grande do Sul, more specificaly, in the towm of Nova Palma. So, since perspective that the Italian Immigrant descendents elect cultural traces which associate them with their ancestors and with the Italy, the material culture and immaterial elements become cultural patrimony that will may find the place of their materialization. Parting this, one preservation forms of mencionated patrimony is the museum, comprehend how the memory place that interaleds and presents the community which belong. There fore, to that this community sensibilizeds and understands its social script in to fight by cultural patrimony preservation is fundamental one exposition in this form, this searsh mastership dissertation pretends through of two chapters, with basis in bibliographic source, documents and iconographics, to trate anwers about cultural patrimony conceptions, history, memory and identity as well as to sunthetize the historical process in the towm of Nova Palma, rebound the Centro de Pesquisas Genealógicas importancy as the instituition which might and incentivated the preocupation as the memory preservation and its history. Since this we present a proposal to creation the Municipal Historical Museum and local community sensibilization through exposition, to that integrate the fight for concreteness this instituition.